Digital Da’wah Management and Anti-Hoax Literacy: A Multicultural Local Wisdom Reading: Manajemen Dakwah Digital dan Literasi Anti-Hoaks: Pembacaan Kearifan Lokal Multikultural - Fatmawati Fatmawati; Nunung Khoiriyah; Armawati Arbi; Kalsum Minangsih (UIN Antasari Banjarmasin, 2026)
The proliferation of hoaxes across digital platforms presents a significant challenge for adolescent religious education and contemporary da’wah practice in Indonesia. This study examines digital-based media literacy as a strategic instrument of da’wah management and reads it through a multicultural local-wisdom lens to understand anti-hoax behavior among adolescents. The research employs a quantitative explanatory approach using a cross-sectional survey, distributing questionnaires to 100 students drawn from five State Senior High Schools (SMA Negeri) across the Greater Jakarta metropolitan region, namely Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek), with schools selected purposively and respondents drawn randomly within each school. Data analysis utilized simple linear regression through SPSS version 20.0, followed by an interpretive analysis that maps the statistical findings onto da’wah management functions and the region’s multicultural local wisdom, encompassing Betawi musyawarah-mufakat and gotong royong, Sundanese silih asih, silih asah, silih asuh, alongside the Islamic principle of tabayyun. The findings indicate that digital media literacy is positively and significantly associated with anti-hoax behavior, accounting for 53.8 percent of the variance in the sample. The study positions digital media literacy as a contemporary form of da’wah bil-hikmah operating through systematic planning, organizing, actuating, and controlling functions, with multicultural local wisdom and Islamic ethics serving as an interpretive framework rather than a measured variable. Given the small, purposively selected sample, the findings describe the surveyed students and are not generalizable to all adolescents in Jabodetabek or Indonesia. KEYWORDS digital da'wah management; media literacy; anti-hoax behavior; local wisdom; tabayyun